BlueResilience (Mlimi Wansomba) Validation Workshop ReportBlueResilience (Mlimi Wansomba) Validation Workshop Report - Mudege, N.N.; Kakwasha, K.; Kondowe, J.; Kanyembo, H.; Kuruganti, P.; Gayathri, K. (2025)
This is a workshop report from a workshop hosted by WorldFish in Kafue, Zambia, to validate the BlueResilience Platform, an aquaculture advisory tool that sends climate alerts and advisories to tilapia fish farmers. A total of 17 participants (6 women, 8 youth) participated in the training. At the end of the workshop, participants who included lead farmers, SMEs, and platform managers, had been trained on how the platform works, had validated and revised climate advisory messages in English and two local languages (Chichewa and iciBemba). The Blue Resilience Platform which is currently hosted by WorldFish has reached 19,866 farmers (7,683 women) and of these, 8,813 (2,884 women) are using generated climate advisories to respond to climate risk (see Table 1 on the details of the advisories). WorldFish has trained two Data Managers from the Ministry of Fisheries and Livestock Head Office to take over the administration of the Blue Resilience platform to ensure that more farmers can access the platform and enhance sustainability.